2020
DOI: 10.1016/j.dib.2019.104855
|View full text |Cite
|
Sign up to set email alerts
|

Experimental data on the production and characterization of biochars derived from coconut-shell wastes obtained from the Colombian Pacific Coast at low temperature pyrolysis

Abstract: Biochars are emerging eco-friendly products showing outstanding properties in areas such as carbon sequestration, soil amendment, bioremediation, biocomposites, and bioenergy. These interesting materials can be synthesized from a wide variety of waste-derived sources, including lignocellulosic biomass wastes, manure and sewage sludge. In this work, abundant data on biochars produced from coconut-shell wastes obtained from the Colombian Pacific Coast are presented. Biochar synthesis was performed varying the te… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 40 publications
(11 citation statements)
references
References 6 publications
0
7
0
1
Order By: Relevance
“…en función del tiempo de residencia durante la producción del mismo (Castilla-Caballero et al 2020).…”
Section: Análisis Microscopía Electrónica De Barrido (Sem)unclassified
“…en función del tiempo de residencia durante la producción del mismo (Castilla-Caballero et al 2020).…”
Section: Análisis Microscopía Electrónica De Barrido (Sem)unclassified
“…Energy can be obtained from coconut shells through thermochemical methods such as pyrolysis and gasification. Several authors have researched the pyrolysis of coconut shells, focusing on producing liquid and solid products [2][3][4]. Coconut shells have also been used as a feedstock for conventional gasification processes, aiming to produce synthesis gas [5][6][7][8].…”
Section: Introductionmentioning
confidence: 99%
“…However, the BET surface area of biochar obtained in this work was still in the same range as those of previous studies. According to the results of Castilla-Caballero et al [37], the BET surface area values of biochar derived from coconut shells obtained from the Colombian Pacific Coast were in the range of 9.85 m²•g -1 to 15.75 m²•g -1 after varying pyrolysis temperature and oxygen-feeding content in the pyrolysis reaction. Babatabar et al [35] found that after pyrolyzing lignocellulosic and algal biomasses in a fixed-bed reactor, the BET surface area of coconut shell-derived biochar was 26.22 m²•g -1 .…”
Section: Morphological Observationmentioning
confidence: 95%